Is the sectoral aid allocation within countries need-oriented? - Jens Eger; Hannes Öhler; Alexandra Rudolph (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The paper focuses on an important dimension of donor aid allocation, which has largely been neglected in the empirical literature: the need orientation of donors when deciding on the sectoral composition of their recipient country portfolios. Employing sector-specific need indicators in logit and zero-one inflated beta estimations our results show that the degree of need orientation of donors depends on the sector. While in the sectors of governance, transport, environment protection, sexually transmitted diseases control including HIV/AIDS and emergency response, the analysis clearly points to a need-based allocation of resources, it is striking that need considerations seem not to play a role in the health and water and sanitation sectors. Remarkably, we find evidence for donor coordination within countries, in that donors took other donors' sector activities into account when deciding on the sectoral composition of their country portfolios.
Keywords: 330; Wirksamkeit und Evaluierung